2004
DOI: 10.1007/s00114-004-0513-0
|View full text |Cite
|
Sign up to set email alerts
|

In-nest environment modulates nestmate recognition in the ant Camponotus fellah

Abstract: Multiple behavioral and chemical studies indicate that ant nestmate recognition cues are low-volatile substances, in particular hydrocarbons (HCs) located on the cuticular surface. We tested the hypothesis that in the ant Camponotus fellah, nest environment, in particular nest volatile odors, can modulate nestmate-recognition-mediated aggression. Workers were individually confined within their own nest in small cages having either a single mesh (SM = limited physical contact permitted) or a double mesh (DM = e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Another study suggested that volatiles could act as short distance discrimination cues in Lasius fuliginosus [54]. Finally in Camponotus fellah , volatiles secreted by the Dufour's gland have been shown to be involved in nestmate recognition [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that volatiles could act as short distance discrimination cues in Lasius fuliginosus [54]. Finally in Camponotus fellah , volatiles secreted by the Dufour's gland have been shown to be involved in nestmate recognition [55], [56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, as nestmates are isolated for a longer time, they face stronger aggression when reintegrated into the colony (Heinze et al. 1996; Katzav‐Gozansky et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This process can lead to the rejection of nestmates that have been kept for long time out of the nest or in a different nest‐site type (e.g., Heinze et al. 1996; Katzav‐Gozansky et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ants, recognition is based in cuticle chemical markers, hydrocarbon molecules synthesized in the colony, that give a particular odor to each nest, which is recognized by the olfactory receptors in the antennae (Lahav et al 1999;Katzav-Gozansky et al 2004).…”
Section: Introductionmentioning
confidence: 99%